2022
DOI: 10.33223/epj/147329
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a grid-connected solar pv system for the electric-vehicle charging station of an office building using pvsol software

Abstract: Electric vehicles are predicted to blossom in Egypt in future years as an emerging technology in both the transportation and power sectors, contributing significantly to the decrease of fossil-fuel usage and CO 2 emissions. As a result, to mitigate overloads of the vehicle energy demand on the nation's electric grid, a solar PV system can be used to provide the electricity needs of an EV charging station. This objective of this paper is to present the design, simulation and economic analysis of a grid-connecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Further research can be aimed at developing longer-term programs for the use of drones and virtual reality in the educational process of students from the first year of study and for students of different specialties. Earlier studies on the value of virtual reality learning environments show an increase in the number of learning environments that use virtual reality specifically for certain specialties such as agronomy and agriculture, geography, and ecology [73], [74], [75], [76], [77]. This study has revealed the effectiveness of VR and drones in the fields of IT technology, architecture and urban planning, engineering, robotics, and journalism.…”
Section: Discussionmentioning
confidence: 84%
“…Further research can be aimed at developing longer-term programs for the use of drones and virtual reality in the educational process of students from the first year of study and for students of different specialties. Earlier studies on the value of virtual reality learning environments show an increase in the number of learning environments that use virtual reality specifically for certain specialties such as agronomy and agriculture, geography, and ecology [73], [74], [75], [76], [77]. This study has revealed the effectiveness of VR and drones in the fields of IT technology, architecture and urban planning, engineering, robotics, and journalism.…”
Section: Discussionmentioning
confidence: 84%
“…Abdullah Al Mehadi [2] this study presents the design, simulation, and analysis of the monofacial photovoltaic module installed on the roof of the residence hall in IUT's North Hall. Three separate pieces of software were used to construct and assess a comprehensive 3D design [3]- [5]. According to a research paper [6], electric vehicle technology is now developing quickly and could eventually supplant conventional autos.…”
Section: B Literature Surveymentioning
confidence: 99%
“…The battery-free system showed the most significant decrease in GHE, totaling 137,321,924 kg of CO 2 . In October 6 City, Egypt, as described by Ibrahim [79], used PV-SOL to give a tech-economic study of a 5.9 kW grid-connected PV system for an electric charging station at a workplace. Electricity fueled the appliances in the office buildings and charging stations.…”
Section: Environmental Impacts Of Solar or Wind-powered Ev Chargingmentioning
confidence: 99%
“…In total, 87% of the power is resold to the grid. In October 6 City, Egypt, Ibrahim [79] considered a tech-economic study of a 5.9 kW grid-connected PV system for an electric charging station at a workplace. The annual PV energy production was determined to be 10,463 kWh, with an annual efficiency of 1786.69 kWh/kW.…”
Section: Economic Metrics For Evcss Powered By Solar or Wind Energymentioning
confidence: 99%